Ferroelétricos relaxores canônicos: um estudo a partir do efeito eletro-óptico em função da temperatura - Milton, Flávio Paulo (2013)
This study revisits the lanthanum-modified lead zirconate titanate ferroelectric relaxor system (PLZT) by investigating its electro-optical properties, particularly the variation of birefringence induced by electrical field, n(E). The thermal evolution of n(E), obtained by the Kerr (quadratic) and Pockels (linear) electro-optical effects, was considered in the verification of possible critical temperatures predicted for the transitions between the paraelectric (PE), ergodic ferroelectric relaxor (EFR), non-ergodic ferroelectric relaxor (NEFR), and normal ferroelectric (FE) states. Such temperatures identify the regions that separate different correlation states (static and dynamic) from the polar nano-regions (PNR) present in these materials. This work made use of ceramics La/Zr/Ti = 9/65/35, which are located on the tricritical point of the PZLT phase diagram. The effect of doping with 1% weight of rare-earth oxides (Nd, Ho, Er, Tm e Yb) upon the relaxor behaviour was also investigated. The undoped material was used as a reference system in the elaboration of a protocol for data collection and treatment, which included the results of ferroelectric, dielectric and pyroelectric measurements. The n(E) results obtained for the quadratic response (Kerr effect) as a function of temperature were suitable for determining the freezing temperature (Tf) associated to the FE-FRE transition or to the FRE-FRNE transition, as well as the temperature associated to the maximum electrical permittivity (Tε′m), and the Burns temperature (TB) associated to the FRE-PE transition. Conversely, the dependence of n(E) to linear response (Pockels effect) as a function of temperature proved sensitive for determining the characteristic temperature T*, which indicates the initial temperature for a correlated state of short and mid-range NRP reach during cooling of the material. All of these characteristic temperatures could be determined for the doped PLZT system as well, and the same behaviours were observed for the Kerr and Pockels electro-optical responses. It is worth noting that this is the first time the n(E) linear effect response is applied to the analysis of this system. However, the transition intervals between polar and non-polar states suffered changes according to rules associated to the difference between the ionic radii of rare-earth and the cation that had been replaced in the crystal structure. Although the ferroelectric, electric, dielectric, pyroelectric, and electro-optical properties of the PLZT system were clearly affected by doping, no significant changes in the relaxor behaviour could be observed.